The safety of atezolizumab plus chemotherapy for the treatment of metastatic lung cancer. Issue 7 (2nd July 2020) - Manzo, Anna; Carillio, Guido; Montanino, Agnese; Sforza, Vincenzo; Palumbo, Giuliano; Esposito, Giovanna; Costanzo, Raffaele; Sandomenico, Claudia; La Manna, Carmine; Martucci, Nicola; La Rocca, Antonello; De Luca, Giuseppe; et al.
ABSTRACT: Introduction: Atezolizumab is a humanized monoclonal antibody against PD-L1 capable of enhancing antitumor immune activity, with a demonstrated activity as single agent in patients with advanced non-small-cell lung cancer (NSCLC). Areas covered: This review summarizes the clinical data emerging from randomized clinical studies with atezolizumab in NSCLC and small-cell lung cancer (SCLC), focusing in particular on the efficacy and safety data regarding the combinations of atezolizumab plus chemotherapy in the IMpower studies. Expert opinion: A significant improvement in progression-free survival and in overall survival was observed in IMpower 130 and 150 (NSCLC non-squamous) and 133 (SCLC), with an acceptable safety profile. In particular, the most common immune-related adverse events were rash (18–28% of patients), hypothyroidism (8–15%), hepatitis (5–17%), pneumonitis (2–7%), and colitis (1.5–2.3%). The safety profile of atezolizumab in combination with chemotherapy was consistent with the known adverse events related to single-agent atezolizumab and no new adverse events were observed. Ongoing studies will evaluate the role of atezolizumab in other settings (adjuvant and neoadjuvant) and in combination with chemotherapy and radiotherapy for patients with locally advanced NSCLC and the role of predictive factors (B-FAST study).